In-hospital cardiac rehabilitation and clinical outcomes in patients with acute myocardial infarction after percutaneous coronary intervention: a retrospective cohort study - Hiroaki Iijima; Kiyohide Fushimi; Natsuko Kanazawa (BMJ Open)
Objectives To verify the associations between participation in an in-hospital cardiac rehabilitation (CR) programme and clinical outcomes among patients with acute myocardial infarction (AMI) after percutaneous coronary intervention (PCI).Design A retrospective cohort study using the Japanese administrative claims database.Setting Japanese acute-care hospitals.Participants Patients aged ≥18 years who underwent PCI due to AMI and survived to discharge.Primary and secondary outcome measure The primary outcomes were revascularisation, all-cause readmission and cardiac readmission (median follow-up period: 324 days, 236 days and 263 days, respectively). The secondary outcomes were all-cause mortality and cardiac mortality (median follow-up period: both were 460 days).Result The data of 13 697 patients were extracted from the database, and 65.4% of them participated in an in-hospital CR. The risks of revascularisation, all-cause readmission and cardiac readmission among CR participants were compared with those of non-participants using two statistical techniques: matched-pair analysis based on propensity score and a 30-day landmark analysis. The results of those analysis were consistent and showed that the CR participants had lower risk of revascularisation (adjusted HR: 0.74; 95% CI: 0.65 to 0.84), all-cause readmission (HR: 0.81; 95% CI: 0.74 to 0.88) and cardiac readmission (HR: 0.77; 95% CI: 0.70 to 0.85). However, all-cause mortality and cardiac mortality were not associated with participation in the CR.Conclusions It was suggested that in-hospital CR participation may reduce the risk of revascularisation, all-cause readmission and cardiac readmission among patients with AMI after PCI. In-hospital CR may expand the potential benefits of CR in addition to outpatient CR.